Personalized immunotherapy (AGS-003) when combined with sunitinib for the treatment of metastatic renal cell carcinoma. (August 2015) - Figlin, Robert A
<x xml:space="preserve">Abstract</x> Introduction: <ext-link ext-link-type="uri" xlink:href="http://informahealthcare.com/action/doSearch?type=advanced&displaySummary=true&displaySummary=true&field1=keywords&text1=AGS-003&logicalOpe1=OR&field2=articletitle&text2=AGS-003&logicalOpe2=AND&field3=all&text3=&search=Search&categoryId=41010274&categoryId=40002416&categoryId=40004717&categoryId=40004717&filter=multiple&AfterMonth=1&AfterYear=&BeforeMonth=12&BeforeYear=&sortBy=date&nh=20" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink">AGS-003 is a novel autologous dendritic cell vaccine currently in Phase III clinical development in combination with sunitinib for patients with intermediate- and poor-risk clear cell metastatic renal cell carcinoma (ccmRCC). Areas covered: In addition to research published within the past 15 years demonstrating the efficacy of novel targeted therapies, early-phase clinical trial results recently published for AGS-003 in combination with sunitinib are discussed, as well as the ongoing Phase III clinical trial Autologous Dendritic Cell Immunotherapy (AGS-003) Plus Standard Treatment of Advanced Renal Cell Carcinoma. Expert opinion: AGS-003 in combination with sunitinib is a rational step forward for the clinical management of patients with ccmRCC. If the Phase III Advanced Renal Cell Carcinoma trial is positive, this treatment modality will provide a significant survival benefit with minimal toxicity and could change the standard of care for ccmRCC.